Critical Proximity: Refiguring Research Cultures in The Design Curriculum - Kruth, Jeffrey; Keslacy, Elizabeth (Enquiry The ARCC Journal for Architectural Research, 2022)
The architecture curriculum is usually divided into studio courses and lecture or seminar courses where design and research, respectively, are separately pursued. Although the curriculum is designed to unite the approaches of design, the humanities, and the sciences that together comprise the architectural endeavor, in practice these epistemological forms of inquiry are divided into separate courses and rarely allowed to crossover into one another. Two structures common to architecture programs avoid these divisions: the community design center and the research studio. The first unifies design with community engagement and exposure to the real-world issues of marginalized communities, while the second incorporates humanities-based research into the studio. In this paper, we will present the work of a three course-sequence recently taught at Miami University as a “Humanities Lab” that pursued methodological promiscuity by mixing community-based research and design. In so doing, we jettisoned the expertise traditionally claimed by architecture to create a more inclusive practice–inclusive of community members and their expertise and centering the experiences and histories of marginalized people instead of buildings. We do so by engaging in what Eyal Weizman has called “critical proximity,” in which the distanciated position of the researcher is jettisoned in favor of working alongside and for marginalized communities. Over the course of three semesters, we explored the impact of critical proximity in three different endeavors–a seminar, research studio, and exhibition design–and discovered inclusive pedagogical strategies: thickness, research-in-community, and decentered production. Together, these strategies allowed us to refigure the role of the architect as a researcher aligned with community interests.